ИЗУЧЕНИЕ ЗНАЧЕНИЯ ОГРАНИЧЕНИЯ В ПРОСТРАНСТВЕ В ЯЗЫКАХ РАЗЛИЧНЫХ СИСТЕМ - Хошанов, Б.Х. (SCIENCE and SOCIETY, 2016)
The article is devoted to the study of the meaning of limitation in space in the languages of the different systems in Russian and Karakalpak. The methods of transmission of the meaning of limitation in space in Russian by constructions with a preposition «to» and their equivalents in the Karakalpak language have been studied in the article.
Keywords: case; preposition; space; word, combination; direction; object; verb of motion; suggestion; equivalent; limitation; construction; prefix